Protections for the Portion Reserved Against Marital Property Agreements and an Evaluation of the Amendments Relevant to the Swiss Civil Code - Kemal Erdoğan (İstanbul Hukuk Mecmuası)
According to Paragraph 1 from Article 202 of the Turkish Civil Code (TCC), the shared re-gime in acquired property is essential. However, spouses may accept one of the types of marital property regimes legally regulated through a marital property agreement, or they may make changes to the provisions of these limited number of regimes. In this case, the issue comes to the fore of whether priority should be given to the marital property agreement or to protecting the reserved portion. The basic principle accepted by Turkish legislation is that any marital property agreement concluded between spouses takes precedence over the interests of heirs with a reserved share. While Section II under Article 237 of the TCC protects the reserved share of non-common children and their descendants against marital property agreements in which a different principle regarding the shares of the residual value have been accepted, Section III under Article 276 of the TCC protects the offspring family’s reserved shares against property regime agreements regarding any other manner of distributing a partnership property. Both provisions have been criticized doctrinally on the grounds that they disrupt equality among heirs with reserved shares. On the other hand, a revision was made in the field of inheritance law in Switzerland, and these provisions entered into force on January 1, 2023. The revision amends and supplements part of the provisions included in Article 216 and 241 of the Swiss Civil Code (SCC). In light of these changes, the need has arisen to reconsider the issue.